Relation Between Sport and Spatial Imagery: Comparison of Three Groups of Participants. - Ozel, Sylvie; Larue, Jacques; Molinaro, Corinne (Journal of Psychology, 2004)
The literature suggests that sport may be considered a spatial activity and that engaging in spatial activities increases the capacity of an individual to implement mental imagery. Moreover, mental rotation calls upon motor processes that are heavily involved in sporting activities. For these reasons, the authors hypothesized that athletes ought to perform mental rotation tasks better than nonathletes. Also, athletes trained to react quickly to constantly changing environments should be faster at processing the information in a mental rotation task than athletes operating in more settled environments. The results of this study show that athletes performed the mental rotation task significantly faster than nonathletes. These results support the suggestion that there is a link between sport and the ability to perform mental image transformations; however, this ability may not be specific to the conditions in which the athlete performs. Reprinted by permission of the publisher.